Measuring emotion: A new evaluation tool for very young children - Mohd Yusoff, Yusrita; Ruthven, Ian; Landoni, Monica (2013)
In this paper, we report our experience researching with very young children (age 3 to 5 years old) in a series of evaluation study in one local nursery in the UK.A new evaluation tool, named the Fun Semantic Differential Scale (FSDS) has been developed and tested with the nursery children to understand how they respond to it.We report on our experience of using these scales to evaluate the fun experienced by children after inter-acting with computer products.